EFFECTIVENESS OF USE DIALIZER REUSE ON UREA REDUCTION RATIO IN HEMODIALYSIS PATIENTS AT KARSA HUSADA BATU HOSPITAL - Anik Suntiari; Wiwik Agustina; Sih Ageng Lumadi (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2022)
Chronic Kidney Disease (CKD) is an end-stage disease of the kidneys, the causes are multiple, can cause to uremia and cannot be renewed. Hemodialysis is a therapy for renal kidney disease. One of the appraisal adequacy of hemodialysis therapy is to use the URR (Urea Reduction Ratio) that assessment by measuring urea before and after hemodialysis therapy. Hemodialysis therapy uses a dialyser that can be used repeatedly in the same patient. The use of dialysers at Karsa Husada Batu Hospital can be used up to 7 times reuse. The research objective was to determine the effectiveness of using a reuse dialyzer to URR. This research design uses comparative descriptive appraisal is a difference between reuse to 1,3,5,7 and using a cross-sectional approach. Sampling using purposive sampling with a sample size of 26 respondents. The different test was used Kruskal Wallis by assessing the URR at the dializer in 1,3,5,7 reuse. Significance of 0.802 (p> 0.05) was obtained, which means that there is no significant difference in the URR value of chronic renal disease patients with hemodialysis therapy using dialyzer reuse to 1,3,5,7. For the URR assessment, it has decreased and increased but is still in normal limits. The dializer reuse up to seven can still be said to be effective in accordance with the guidelines for the management of End-Stage Renal Disease. It is hoped that there will be studies investigating the factors that affect the total volume dilation of dialyser reuse.Keywords : Hemodialysis, Dialyzer Reuse , Urea Reduction Ratio